Theoretical knowledge and utilization of the theory of comfort in nursing practice - Aguayo-Verdugo, Natalia (Universidad de Sonora, 2019)
Introduction: For years, Nursing has struggled to get the recognition as being a discipline in which the own theoretical knowledge and practice based on evidence are fundamental requirements. Objectives: 1) Identify knowledge about general and midrange nursing theories (TRM by its acronym in Spanish), its utilization in practice and examples of application of the Kolcaba comfort theory in the nursing activities in the Anesthesia and Recovery Ward at a hospital in Concepción; 2) Perform an educational intervention as continuous training of these professionals. Methodology: Intervention pilot project in educational management, performed between April and May of 2017, including the application of initial questionnaire, followed by education and focus group, finishing with a final questionnaire. Results: Participation of 11 nurses. Knowledge prior to the intervention was scarce in regards to big theories and null about TRM. The nursing theories were defined as basis of the professional activities, but only four (4) of the 11 professionals recognized using them daily. After educational intervention, examples of the application for the Kolcaba theory where identified; physical comfort: pain assessment and management; psychospiritual comfort: direct communication with the patient, explaining processes to go through; sociocultural comfort: informing the family; environmental comfort: reduction of the intensity of the lights, noises, and or conversations. Conclusions: It is recommended to perform interventions in order to reinforce knowledge about nursing and encourage formation of work groups between clinic nurses and scholars in order to carry out research, looking to reduce the existence gap between theoretical and practical knowledge.